360º content, virtual reality and immersive journalism: a current review of media using these formats - García Caballero, Sara (2021)
The 360º multimedia format and virtual reality help the journalist to take journalistic coverage to another dimension, as some media like The New York Times, USA Today or Euronews have already been doing. New narratives are enabling a transformation in access to information, as well as an expansion of audiences. However, the boom in these formats since 2014, pushed by tech giants such as Google and Facebook, has been suffering a halt since 2017 and only a few referents continue to be on these pieces. Because of this, the study proposes a tour of the national and international media that currently use 360º videos and virtual reality as an information method, using the qualitative methodology of the case study. It is noted that there has been a significant decline and that one of the causes may be the lack of technological literacy around the issue.